2005
DOI: 10.1002/bjs.4947
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plasma N-terminal pro-brain natriuretic peptide as a marker of cardiac risk in patients undergoing elective non-cardiac surgery

Abstract: Preoperative plasma NTproBNP concentration may be an independent predictor of cardiac complications in patients undergoing non-cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 28 publications
5
54
0
1
Order By: Relevance
“…The predictive value of BNP ⁄ NT-pro-BNP for MACE following vascular surgery The results presented in this meta-analysis allow the reader to compare the performance of pre-operative BNP or NT-pro-BNP with meta-analytical data presented for Short-term studies Yeh [12] Short term (to discharge < 30 days) NT-pro-BNP 450 **** * *** Berry [13] Short term (48 h) BNP 100 **** * *** Cuthbertson [14] Short term (30 days) BNP 40 **** * *** Feringa [6] Short term (30 days) NT-pro-BNP 533 **** * *** Mahla [15] Short term (30 days) NT-pro-BNP 280 **** * *** Intermediate-term studies Cuthbertson [11] Intermediate term (180 days) BNP 35 **** * *** Feringa [7] Intermediate term (180 days) NT-pro-BNP 319 **** * *** Mahla [15] Intermediate term (180 days) NT-pro-BNP 280 **** * *** ambulatory ECG, exercise ECG, radionuclide ventriculography, myocardial perfusion scintigraphy, dypridamole stress echocardiography and dobutamine stress echocardiography in vascular surgical patients [2]. Dobutamine stress echocardiography was reported to have a sensitivity and specificity of 85% (95% CI 74-97%) and 70% (95% CI 62-79%) respectively for the prediction of 30-day MACE in vascular surgical patients [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The predictive value of BNP ⁄ NT-pro-BNP for MACE following vascular surgery The results presented in this meta-analysis allow the reader to compare the performance of pre-operative BNP or NT-pro-BNP with meta-analytical data presented for Short-term studies Yeh [12] Short term (to discharge < 30 days) NT-pro-BNP 450 **** * *** Berry [13] Short term (48 h) BNP 100 **** * *** Cuthbertson [14] Short term (30 days) BNP 40 **** * *** Feringa [6] Short term (30 days) NT-pro-BNP 533 **** * *** Mahla [15] Short term (30 days) NT-pro-BNP 280 **** * *** Intermediate-term studies Cuthbertson [11] Intermediate term (180 days) BNP 35 **** * *** Feringa [7] Intermediate term (180 days) NT-pro-BNP 319 **** * *** Mahla [15] Intermediate term (180 days) NT-pro-BNP 280 **** * *** ambulatory ECG, exercise ECG, radionuclide ventriculography, myocardial perfusion scintigraphy, dypridamole stress echocardiography and dobutamine stress echocardiography in vascular surgical patients [2]. Dobutamine stress echocardiography was reported to have a sensitivity and specificity of 85% (95% CI 74-97%) and 70% (95% CI 62-79%) respectively for the prediction of 30-day MACE in vascular surgical patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…and for three of the five short-term outcome studies [12,14,15]. With the exception of one study [6], cardiac death and nonfatal MI were reported in all other shortterm studies.…”
Section: ó 2008 the Authorsmentioning
confidence: 92%
See 3 more Smart Citations